Snow droughts amplify compound climate extremes over the Tibetan Plateau - Wenqing Zhang; Liu Liu; Haijiang Wu; Ting Zhang; Yudong Chen; Lei Wang (Communications Earth & Environment)
Abstract Escalating impacts of snow droughts have critically threatened hydrological stability and socioeconomic resilience on the Tibetan Plateau, Asia’s alpine water tower. However, the mechanisms linking snow droughts to compound climate extremes remain poorly understood. Here, we presented comprehensive assessment of how snow drought regimes modulated compound climate extremes during the period 1979–2022. We found significant increases in severity for both dry snow droughts and warm snow droughts, with warm types emerging as a dominant driver of snowpack depletion. Dry/warm snow droughts triggered compound dry-hot/pluvial-hot extremes through divergent heat-moisture regulation pathways: surface energy budget imbalances acted as the common trigger, while moisture heterogeneity governed the dry-wet divergence. After snow disappearance, a significant coincidence rate of 0.68 (0.58) for compound dry-hot extremes (compound pluvial-hot extremes) was observed at a 1-month lag time (p < 0.05). These findings necessitate adaptive strategies to mitigate cascading threats to water-ecosystem-socioeconomic systems in the Asian water tower.